Silencing of Long Non-coding RNA SMAD5-AS1 Reverses Epithelial Mesenchymal Transition in Nasopharyngeal Carcinoma via microRNA-195-Dependent Inhibition of SMAD5 - Li, Siwei; Zhao, Bo; Zhao, Haiying; Shang, Cui; Zhang, Man; Xiong, Xiaoxia; Pu, Jinjin; Kuang, Bohua; Deng, Guangrui (Frontiers in Oncology, 2019)
Long non-coding RNAs (lncRNAs) have gained widespread attention in recent years as a key regulator of diverse biological processes, but the knowledge of the mechanisms by which they act is still very limited. Differentially expressed lncRNA SMAD5 antisense RNA 1 (SMAD5-AS1) in nasopharyngeal carcinoma (NPC) and normal samples shown by in silico analyses was selected as the main subject, and then microRNA-195 (miR-195) was suggested to bind to SMAD5-AS1 and SMAD5. Therefore, the purpose of the present study was to investigate the effects of SMAD5-AS1/miR-195/SMAD5 on epithelial-mesenchymal transition (EMT) in NPC cells. High expression of SMAD5-AS1 and SMAD5 but low miR-195 expression were determined in NPC tissues and NPC cell lines by RT-qPCR and western blot analysis. SMAD5-AS1 could up-regulate SMAD5 expression by competitively binding to miR-195 in NPC cells. Loss- and gain-of-function investigations were subsequently conducted in NPC cells (CNE-2 and CNE-1) to explore the role of SMAD5-AS, miR-195 and SMAD5 in NPC progression by assessing cellular biological functions and tumorigenic ability in vivo as well as determining the expression of EMT markers. Downregulation of SMAD5-AS1 or SMAD5 or overexpression of miR-195 led to inhibited NPC cell proliferation, invasion and migration and reversed EMT, enhanced apoptosis in vitro as well as restrained tumor growth in vivo. In conclusion, our findings indicate that silencing of lncRNA SMAD5-AS1 impairs the down-regulation of SMAD5 induced by miR-195, eventually repressing EMT in NPC. Hence, SMAD5-AS1 may represent a potential therapeutic target for NPC intervention.